THE IMPLEMENTATION OF VIDEO VIEWING TO TEACH TARGET LANGUAGE CULTURE FOR MANAGEMENT STUDENTS AT STIE DR. MOECHTAR TALIB - Nurhayati Nurhayati; Tri Angkarini (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2015)
The pusposes of the research was to investigate the students’ perception on the implementation of video viewing to teach target language culture for management students at STIE “Dr. Moechtar Talib” in East Jakarta. The students were in the first year (semester one) during a period of two months in which this study was conducted.The researchers used survey method in this study. Data collection were conducted by taking the test and distributing questionnaires. The data were processed and analyzed by using statistic descriptive, normality test, linearity test, Homogenity test, and hypotheses test. Statistic test uses t test and F test. The research was conducted on 15 November 2014 until 5 February 2015. The research shows that there is not an effect of students perception on the imlementation of video viewing to teach target language culture towards students’ target language competence with the regression analisis: = 88,007 - 0,230 X. Whenever there is a rise in the value of students perception on the imlementation of video viewing to teach target language culture, there will be a decrease in students’ target language competence for 0.230.Keywords: video viewing, target language culture